The storm-impervious financial sector: Offshore services likely booked abroad - Jakob Miethe (DIW Weekly Report, 2020)
The high international capital positions of offshore financial centers (OFCs) have led to increasing research in the area. However, many unanswered questions remain, as OFC activities are secretive by nature and data is sparse. It is, for example, not even clear whether the financial industry actually physically operates on OFCs or if it artificially books services from other countries. Using a new research approach that examines the effects of extreme storm events such as Hurricane Irma on local conditions and financial service activities on small islands, this paper shows that offshore services are likely booked primarily from other countries. If this is the case, the current approach of regulating offshore financial services through regulation targeting the offshore financial center is inherently limited.
Keywords: H26; G15; 330; offshore finance; international capital flows; natural disasters; tax havens